Tradisi bertemu waktu: Hubungan kompleks antara islam dan budaya - Ramdani, Muhammad Naja; Ghozi, Ahmad; Aditama, Muhammad Defry; Wijaya, Ferdi Septian Eka; Faizah, Alicia (Maliki Interdisciplinary Journal, 2025)
Islam and culture are an inseparable unity, both have a relationship with each other. Historically, Islam was a superpower in classical times by combining Islamic teachings which guided the development of civilization in that era. This era occurred during the time of the Prophet Muhammad. Continued until the Caliphate era. The aim of this research is to examine a portrait of the development and progress of Islamic civilization in that era. It is hoped that the results of this research can become learning material for the development of Islamic culture in Indonesia, which is currently often conflicted by several parties. Cultural diversity in Indonesia is a very valuable wealth. Some of this diversity is not the least of which is the legacy of previous ulama which includes the acculturation of local culture with Islamic teachings. This research uses a literature analysis method based on previous literature which has studied the complexity of local culture with Islamic teachings.